Answer:
1.) 6
2.) -1
3.) 36
4.) 1/3
5.) 90
Step-by-step explanation:
1.) -12/a
-12/a -> -12/2
=6
2.) a+ (-b)
a+(-b) -> 2+(-3)
=-1
3.) 3a (12-2b)
3a(12-2b) -> 3(2) (12-2x3)
6(12-6)
6(6)
=36
4.) 2a-c/b
2a-c/b -> 2(2)-5/3
4-5/3
=1/3
5.) 3abc
3abc-> 3x2x3x5
=90
Answer:
No
Step-by-step explanation:
Because they are not proportional they do are not a multiple of each other
You want to know the factor by which 3 2/3 is multiplied to get 7 1/3.
1. You can estimate that it is 2 from 7/3 ≈ 2, then check by multiplication to see if that is right.
.. 2*(3 2/3) = 6 4/3 = 7 1/3 . . . . 2 is the correct factor.
2. You can divide 7 1/3 by 3 2/3 to see what the factor is.
.. (7 1/3)/(3 2/3) = (22/3)/(11/3) = 22/11 = 2 . . . . 2 is the factor Earl used.
3. You could see how many times you can subtract 3 2/3 from 7 1/3.
.. 7 1/3 -3 2/3 = (7 -3) +(1/3 -2/3) = 4 -1/3 = 3 2/3 . . . . . subtracting once gives 3 2/3
.. 3 2/3 -3 2/3 = 0 . . . . . . subtracting twice gives 0, so the factor is 2.
4. You could add 3 2/3 to see how many times it takes to get 7 1/3.
.. 3 2/3 +3 2/3 = (3 +3) +(2/3 +2/3) = 6 +4/3 = 7 1/3
We only need to add two values of 3 2/3 to get 7 1/3, so the factor is 2.
___
We have shown methods using multiplication, division, subtraction, addition. Take your pick.
Answer:
Step-by-step explanation:
(9x-1)^-1/2 - (x+2)(9x-1)^-1/2
= (9x-1)^-1/2( 1 - (x + 2))
= (9x-1)^-1/2(-1 - x)
= -(x + 1)(9x-1)^-1/2
= -(x + 1) / (9x-1)^1/2